2021
DOI: 10.1039/d0nj06159j
|View full text |Cite
|
Sign up to set email alerts
|

Novel ruthenium(iii) complexes with hydroxybenzophenones: experimental and theoretical characterization and in vitro leishmanicidal activity comparing complexes and ligands

Abstract: Herein, novel ruthenium(III) complexes with hydroxybenzophenones with the general formula cis-[RuCl2(HB)(dppb)] were obtained where HB = 2-hydroxy-4-(octyloxy)benzophenone (C1), 2-hydroxy-4-metoxybenzophenone (C2), 2,2'-dihydroxy-4,4'-dimethoxybenzophenone (C3), 2,2′-dihydroxy-4-methoxybenzophenone (C4), 2,4-dihydroxybenzophenone (C5), 2,4,4'-trihydroxybenzophenone (C6), and dppb...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…As shown in Figure , the measured masses ( q e ) of Cr in various MP–Cr–UV filter systems were apparently higher (1.4–5.8 times, Table S6) than those in the MP–Cr systems, implying that MP–Cr interaction was favored by the coexisting UV filter. Such a difference can be understood by integrating knowledge of metal coordination chemistry and multilayer sorption as briefly described as follows: First, model UV filters are derivatives of o -hydroxybenzophenone (Table S1), which are known as chelating ligands that can coordinate with transition metals in a bidentate mode via their carbonyl and phenolate oxygen atoms. The formed Cr–UV filter complexes may exhibit different sorption behaviors with MP particles as compared to the Cr cations. This hypothesis is supported by the findings of Wang and co-workers, , who demonstrated that the formation of Cu–TC complexes significantly increased the Cu uptake by polyethylene MPs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure , the measured masses ( q e ) of Cr in various MP–Cr–UV filter systems were apparently higher (1.4–5.8 times, Table S6) than those in the MP–Cr systems, implying that MP–Cr interaction was favored by the coexisting UV filter. Such a difference can be understood by integrating knowledge of metal coordination chemistry and multilayer sorption as briefly described as follows: First, model UV filters are derivatives of o -hydroxybenzophenone (Table S1), which are known as chelating ligands that can coordinate with transition metals in a bidentate mode via their carbonyl and phenolate oxygen atoms. The formed Cr–UV filter complexes may exhibit different sorption behaviors with MP particles as compared to the Cr cations. This hypothesis is supported by the findings of Wang and co-workers, , who demonstrated that the formation of Cu–TC complexes significantly increased the Cu uptake by polyethylene MPs.…”
Section: Resultsmentioning
confidence: 99%
“…From this, it is clearly seen that on both PSMPs the BP-type UV filters with more −OH groups within each pair (i.e., BP-2 and BP-8) exhibited a relatively higher Cr­(VI) abundance. A possible explanation for this phenomenon is that the two UV filters contain an additional ortho -hydroxyl group in their benzene rings, which in turn favors their bidentate coordination with Cr­(III) cations, and thus, more Cr­(III)–organic complexes are formed and being oxidized on the surfaces of PSMPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasites were counted daily in Neubauer chamber for ve days. When they reached the stationary phase of growth, new in vitro passages of the parasites were performed (Dias et al 2021).…”
Section: Parasite Culturementioning
confidence: 99%